A 2.45GHz CMOS PA+T/R switch for wireless communication - Hu, Changhui (2008)
This thesis describes the design of an RF CMOS Power Amplifier (PA) combined with a T/R switch in a conventional CMOS process. The Power Amplifier is designed for all applications in the ISM (Industry Science and Medical) band, which has a transmit frequency of 2.4~2.4835 GHz and requires a peak output power of 100mW (EIRP). A Class A CMOS PA with T/R switch in a 0.18um thick gate standard CMOS process which can generate 100mW of output power into a 50ohms load is presented in this report. Packaging, PCB and testing issues are also described in this report.